Dictionary of archaeological terms English-German / German-English = Archäologisches fachwörterbuch : Englisch-Deutsch / Deutsch-Englisch - Junghans, Marie-Christine (Archaeopress, 2012)
This concise dictionary is intended to be helpful in the reading of archaeological books and publications, and in the writing of papers and articles in both English and German.